Peningkatan Kemampuan Penulisan Surat Dinas para Pegawai Administrasi - Malasari, Tiarma Nova Intan (Multiverse: Open Multidisciplinary Journal, 2024)
This study focuses on the challenges of writing official letters in accordance with correct and proper language guidelines. The background of this research includes difficulties in composing official letters that adhere to the guidelines, understanding language rules (PUEBI, TBBI), and using appropriate language in writing official letters. The study offers three solutions: (a) conducting academic studies, simplifying the guidelines, and contextualizing them; (b) providing assistance in the form of small groups to apply language rules in composing official letters so that PUEBI can be implemented; (c) providing guidance and training in writing official letters using proper, logical, informative, and unambiguous language. The research methodology employs a problem-solving approach combined with focus group discussions (FGD), beginning with an analysis of conditions and problems, formulating directed problems, implementing problem-solving training for letter writing, and conducting evaluations.